Rdna ITS1 SEQUENCE ANALYSIS BASED GENOTOXICITY ASSESSMENT OF DICOFOL BY USING CULEX QUINQUEFASCIATUS (DIPTERA: CULICIDAE) - LOVLEEN, (International Journal of Pharma and Bio Sciences, 2015)
Present research work is attributed to mutagenicity assessment of dicofol by using Culex quinquefasciatus, exposed to LC20 for 24 hours. To achieve present targets, rDNA ITS1 sequence of treated as well as control individuals was amplified by using specific forward and reverse primers with sequences FR 5´-C C T T T G T A C A C A C C G C C C G T-3´ and RP 5´-G T T C A T G T G T C C T G C A G T T C A C-3´. Sequence alignment of treated and control stocks was done by the Clustal W software programme, subsequently it was observed that dicofol induced a total of 334 alterations in rDNA ITS1 sequence, which included 33 deletions, 49 additions, 120 transitions and 132 transversions. Futhermore, dicofol caused maximum deletions and additions of cytosine base.